Initial Hearing Preservation Is Correlated With Cochlear Duct Length in Fully-inserted Long Flexible Lateral Wall Arrays. Issue 8 (September 2021) - Hollis, Emily S.; Canfarotta, Michael W.; Dillon, Margaret T.; Rooth, Meredith A.; Bucker, Andrea L.; Dillon, Sarah A.; Young, Allison; Quinones, Kristen; Pillsbury, Harold C.; Dedmon, Matthew M.; O'Connell, Brendan P.; Brown, Kevin D.
Abstract : Objectives: To characterize the relationship between cochlear duct length (CDL) and initial hearing preservation among cochlear implant recipients of a fully inserted 31.5 mm flexible lateral wall electrode array. Study Design: Retrospective review. Setting: Tertiary academic referral center. Patients: Adult cochlear implant recipients who presented preoperatively with unaided hearing detection thresholds of ⩽ 65 dB HL at 125 Hz and underwent cochlear implantation with a 31.5 mm flexible lateral wall array. Intervention: Cochlear implantation with a hearing preservation surgical approach. Main Outcome Measures: Computed tomography was reviewed to determine CDL. Hearing preservation was characterized by the shift in low-frequency pure-tone average (LFPTA; 125, 250, and 500 Hz), and shift in individual unaided hearing detection thresholds at 125, 250, and 500 Hz. Results: Nineteen patients met the criteria for inclusion. The mean CDL was 34.2 mm (range: 30.8–36.5 mm). Recipients experienced a mean LFPTA shift of 27.6 dB HL (range: 10–50 dB HL). Significant, negative correlations were observed between CDL and smaller threshold shifts at individual frequencies and LFPTA ( p ⩽ 0.048). Conclusion: A longer CDL is associated with greater likelihood of preserving low-frequency hearing with long arrays. Low-frequency hearing preservation is feasible with fully inserted long flexible arrays within the initial months after cochlear implantation. Preoperative measurement of CDL may facilitate a more individualized approach in array selection to permit optimal cochlear coverage while enhancing hearing preservation outcomes.